Identification of novel circulatory microRNA signatures linked to patients with ischemic stroke. (25th April 2018) - Vijayan, Murali; Kumar, Subodh; Yin, Xiangling; Zafer, Dila; Chanana, Vishal; Cengiz, Pelin; Reddy, P Hemachandra
Abstract: MicroRNAs (miRNAs) are involved in growth, development, and occurrence and progression of many diseases. MiRNA-mediated post-transcriptional regulation is poorly understood in vascular biology and pathology. The purpose of this is to determine circulatory miRNAs as early detectable peripheral biomarkers in patients with ischemic stroke (IS). MiRNAs expression levels were measured in IS serum samples and healthy controls using Illumina deep sequencing analysis and identified differentially expressed miRNAs. Differentially expressed miRNAs were further validated using SYBR-green-based quantitative real-time PCR (qRT-PCR) assay in postmortem IS brains, lymphoblastoid IS cell lines, oxygen and glucose deprivation/reoxygenation -treated human and mouse neuroblastoma cells, and mouse models of hypoxia and ischemia (HI)-induced stroke. A total of 4656 miRNAs were differentially expressed in IS serum samples relative to healthy controls. Out of 4656 miRNAs, 272 were found to be significantly deregulated in IS patients. Interestingly, we found several novel and previously unreported miRNAs in IS patients relative to healthy controls. Further analyses revealed that some candidate miRNAs and its target genes were involved in the regulation of the stroke. To the best of our knowledge, this is the first study identified potential novel candidate miRNAs in IS serum samples from the residents of rural West Texas. MiRNAs identified in this study could potentially be used as a biomarker and the development of novel therapeutic approaches for stroke. Further studies are necessary to better understand miRNAs-regulated stroke cellular changes.